Price Trend Studies of Teak Logs Taku Depot (Madhya Pradesh) - Suri, S. K. (Indian Forester, 1974)
Systematic analyais of auction results is essential to understand the dynamics of price tread. In this paper an attempt has been made to analyse the auction results of teak grade-II logs of Taku Depot for the years 1970-71 and 1971-72. The analysis reveal that highest rates are obtained in July auction; second or third auction usually retch lower rates than first auction of the year; there Is definite tread in price rise with lengths girth remaining same; and the price rise trend durind 1971-72 was 3.4% over 1970-71.